Animal-based gelatine and cheesemaking / Nur Shahida Mohamed … [et al.] - Mohamed, Nur Shahida; Azman, Norshahira; Mohd Ali, Nursy Ahida; Patul Muin, Fairuz Irdina; Azhan, Siti Khairul Aisyah (2023)
In today's world, there are many types of food that have illegal sources and the community, especially Muslims, question the halal logo found on the food plastic. This situation has raised issues and doubts among Muslims. There is also the issue of making cheese and gelatine from animals. In fact, there is no denying the issue of gelatine from animals that is a source of contention among the Muslim community. This is where the President of the Association of Sunnah Waljamaah Malaysia (ASWAJA), namely Zamihan Mat Zin, criticized the opinion of scholars who came up with a "perverse fatwa" that food containing pork gelatine is halal for Muslims. Furthermore, he also wants the authorities to prosecute those who have spread such beliefs in Malaysia on the grounds that they are contrary to the evidence of the Al-Quran and the beliefs of Ahli Sunnah Wal Jamaah and called for the religious authorities to investigate and take action gainst any individual who often sparked controversy and issued perverse religious fatwa.